PENGARUH MANAJEMEN MUTU TERPADU DAN MANAJEMEN RANTAI PASOKAN TERHADAP KINERJA OPERASIONAL PT. BERKAT JAYA MAKMUR ABADI - Mario Yehezkiel Regar; Wiwik Rachmarwi (Jurnal Manajemen Bisnis Krisnadwipayana, 2022)
This study aims to analyze and determine the effect of total quality management and supply chain management on operational performance. The sample used a non-probability sampling method, and the data collected was obtained by means of a questionnaire. It was then analyzed using a quantitative method. The results showed that, together, total quality management and supply chain management have a partial and simultaneous effect on operational performance at PT. Berkat Jaya Makmur Abadi.